Analisis Perbandingan Kinerja Keuangan dan Return Saham PT Indosat Ooredoo Hutchison Tbk Sebelum dan Sesudah Merger dari Tahun 2019-2024 - Wahyugianto, Rangga Rizky; Aminah, Indianik (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The rapid growth of digital technology and increasing demand for data services have intensified competition in Indonesia's telecommunications industry. To enhance operational efficiency and strengthen market position, PT Indosat Tbk merged with PT Hutchison 3 Indonesia, effective on January 4, 2022. However, the impact of this corporate action on financial and market performance remains unclear. This study aims to analyze the differences in financial performance and stock returns of PT Indosat Ooredoo Hutchison Tbk before and after the merger over a six-year period, divided into three years pre- and post-merger (2019 - 2024). The analysis focuses on seven financial indicators: Current Ratio (CR), Fixed Asset Turnover (FAT), Total Debt to Total Capital (TDTC), Return on Invested Capital (ROIC), Price to Earnings Ratio (PER), Economic Value Added (EVA), and Market Value Added (MVA), along with stock return as a market performance indicator. A paired sample t-test was used to evaluate statistical differences. The results show a significant increase in FAT, indicating improved asset utilization, and a significant decline in MVA, reflecting weakened market perception after the merger. The other five financial ratios and stock return did not demonstrate statistically significant changes. These findings suggest that while operational efficiency has improved in certain aspects, the merger has not yet resulted in broad financial or market performance enhancements. The study provides insights for corporate decision-makers and investors in assessing post-merger effectiveness.